2022
DOI: 10.3389/fendo.2022.911079
|View full text |Cite
|
Sign up to set email alerts
|

Activation Versus Inhibition of IGF1R: A Dual Role in Breast Tumorigenesis

Abstract: Historically, the body of literature surrounding the insulin-like growth factor type 1 receptor (IGF1R) has described a largely pro-tumorigenic role in breast cancer cells and in several transgenic or xenograft mouse models of breast cancer. Interestingly, however, more recent evidence has emerged that suggests an additional, previously undescribed, tumor and metastasis suppressive function for IGF1R in both human breast tumors and mammary oncogenesis in mice. These seemingly conflicting reports can be reconci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Recently, we used the human METABRIC database to stratify low and high IGF1R expressing tumors with lymph node positivity, a readout of early-stage metastasis. These analyses revealed that lymph node positivity is ~20% higher in human breast tumors with low IGF1R expression versus those with high IGF1R expression ( 9 ). Our previous studies reported IGF1R expression levels in human tumors are inversely correlated with several key target genes that alter the tumor microenvironment ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we used the human METABRIC database to stratify low and high IGF1R expressing tumors with lymph node positivity, a readout of early-stage metastasis. These analyses revealed that lymph node positivity is ~20% higher in human breast tumors with low IGF1R expression versus those with high IGF1R expression ( 9 ). Our previous studies reported IGF1R expression levels in human tumors are inversely correlated with several key target genes that alter the tumor microenvironment ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“… Model for how Reduced IGF1R in Human Breast Tumors (left) and in Mouse Basal-Like Mammary Tumors results in Enhanced Metastasis. The overview panel (left) summarizes human breast cancer data showing inverse correlation between IGF1R expression and patient survival and lymph node positivity [see ( 9 , 17 )] and from METABRIC data analyses in the current manuscript showing low tumor IGF1R expression is correlated with gene expression indicating increased tumor cell invasion properties and cell cycle and decreased cell adhesion. Similar pathways were identified from scRNA-Seq of the tumors in the mouse models with reduced IGF1R signaling or expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we believe that the negative outcomes of recent clinical trials, despite the obvious disappointment, were critically analyzed and important lessons were learned (26,184,185). Among other possible causes, a retrospective evaluation points out at a fierce competition between pharma companies as one of the reasons that hampered the development of efficient IGF1R drugs.…”
Section: Concluding Remarks: Future Igf Research and The Clinicsmentioning
confidence: 99%
“…In mice, IGFs, IGFBPs, and IGF1R are expressed in the virgin and the developing mammary gland, and cell-specific expression patterns have been described for IGFBPs ( Wood et al, 2000 ). The permissive role of the IGF1R for normal development, duct branching, and alveologenesis of the mouse mammary gland has recently been reviewed in great detail ( Bulatowicz and Wood, 2022 ). While IGF1 is strictly regulated by GH, IGF2 appears to mediate the effects of prolactin during mammary gland development and therefore is required for ductal branching and alveologenesis ( Brisken et al, 2002 ; Hovey et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%